Peran Pemerintah Desa Sukamaju Kecamatan Jonggol dalam Meningkatkan Partisipasi Masyarakat terhadap Pembangunan Fisik Maupun Non Fisik - Holid, Adi; Yustika, Gaung Perwira (Ebisma (Economics, Business, Management, & Accounting Journal), 2023)
Sukamaju Village is one of the villages in Jonggol District, Bogor Regency, which plays an active role in providing space and increasing community participation in village development, both physical and non-physical. This can be seen from the great enthusiasm of the community for all forms of village development, from planning, implementation to supervision, physical and non-physical. This study uses qualitative research with a descriptive analysis approach. This qualitative research seeks to understand certain situations, namely examining the village government's efforts to encourage community participation by involving them in village development, both physical and non-physical. This type of descriptive research is research that contains an overview of situations and events, or ongoing processes. This study aims to find out how important the role of the village government is in arousing the enthusiasm of the community to actively participate in village development, both physical and non-physical in Sukamaju Village, Jonggol District, Bogor Regency.